Syndromic monogenic diabetes genes should be tested in patients with a clinical suspicion of MODY - Colclough, Kevin (Diabetes, 2022)
At present, outside of infancy, genetic testing for monogenic diabetes is typically for mutations in MODY genes that predominantly result in isolated diabetes. Monogenic diabetes syndromes are usually only tested when this is supported by specific syndromic clinical features. It is not known how frequently patients with suspected MODY have a mutation in a monogenic syndromic diabetes gene and thus missed by present testing regimes. We performed genetic testing of 27 monogenic diabetes genes (including 18 associated with syndromic diabetes) for 1280 patients with a clinical suspicion of MODY from routine clinical care that were not suspected of having monogenic syndromic diabetes. We confirmed monogenic diabetes in 297 (23%) patients. Mutations in 7 different syndromic diabetes genes accounted for 19% (95%CI 15-24%) of all monogenic diabetes. The mitochondrial m.3243A>G and mutations in HNF1B were responsible for the majority of mutations in syndromic diabetes genes. They were also the 4(th) and 5(th) most common causes of monogenic diabetes overall. These patients lacked typical features and their diabetes phenotypes overlapped with non-syndromic monogenic diabetes patients. Syndromic monogenic diabetes genes (particularly m.3243A>G and HNF1B) should be routinely tested in patients with suspected MODY that do not have typical features of a genetic syndrome.